Students Sexual Behavior: Local Adultery Regulations and the Risk of Sexual Violence in Malang City - Kumalasari, luluk Dwi; Maksum, Ali; Kriyantono, Rachmat; Chawa, Anif Fatma; Holqi, Fikri Gali Fernando (Journal of Local Government Issues, 2026)
This study aims to investigate the authority of local government and policies regarding adultery and their implications on the risk of sexual violence by reflecting on the sexual behavior of students in Malang. This study uses a qualitative approach with a case study design. The technique for determining subjects uses purposive sampling. Data analysis uses thematic analysis through open coding, axial coding, and pattern coding. The result demonstrates that the Malang City government, through its autonomy function, in its efforts to take action on cases of sexual behavior in Malang City, carries out preventive and repressive measures. This includes the enforcement of regional regulations regarding night entertainment venues, prostitution, and the RPJMD. The jurisdictional boundaries between the campus and local government are often contested, resulting in a lack of synergy in creating public security and order. This is driven by environmental factors and economic needs, with no role for the wider community in prevention efforts, thus contradicting the recognition of legal accommodations that exist in society. The role of the government or relevant stakeholders is necessary in fulfilling aspects of cultural protection, economic fulfillment, and preventive measures through the social environment, so that the focus is not solely on the victims.